Pengaruh Imbangan Tepung Tempe dan Tepung Jagung terhadap Karakteristik BMC Balita - Kelik Putranto; Euis Karlina (Ma'soem University, 2023)
The purpose of this study was to determine the balance of tempeh flour and corn flour against the characteristics of mixed foodstuffs (BMC) for toddlers. This research has been carried out at the Laboratory of Chemistry and Food Processing Technology, Faculty of Agriculture, Ma'some University from October to November 2022. The research method used is an experimental method using a Randomized Group Design (RAK), which consists of 6 treatments and each treatment is repeated 4 times. The treatment tried consisted of a balance of tempeh flour and cornmeal A = 10: 90, B = 20: 80, C = 30: 70, D = 40: 60, E = 50: 50 and F = 60: 40. The results showed that the balance of Tempeh Flour and Corn Flour (60:40) produced Mixed Food Ingredients (BMC) for toddlers which have the characteristics of texture, aroma, taste that are preferred and produce 428.38 kcal of energy for every 100 grams. Mixed foodstuffs made from tempeh flour and cornmeal with a balance (60:40) can be used as an alternative in making toddler BMC.